Methodological Issue of Mitochondrial Isolation in Acute-Injury Rat Model: Asphyxia Cardiac Arrest and Resuscitation - Aoki, Tomoaki; Okuma, Yu; Becker, Lance B.; Hayashida, Kei; Shinozaki, Koichiro (Frontiers in Medicine, 2021)
Background Mitochondrial studies are key to understanding the pathophysiology of cardiac arrest (CA), however there is a potential risk of sampling bias during the mitochondrial isolation process. This study aimed to evaluate the dysregulation of mitochondrial respiratory function after CA while testing the sampling bias induced by the mitochondrial isolation method. Methods and Results Adult rats were subjected to 10-minunte asphyxia-induced CA. Thirty minutes after resuscitation, brain and kidney mitochondria from sham and CA group animals were isolated (n=8, each). The mitochondria quantity, expressed as protein concentrations (isolation yields), was determined and then oxygen consumption rates were measured. ADP-dependent (state-3) and ADP-limited (state-4) respiration activity were compared between the groups. The mitochondrial quantity was evaluated by citrate synthase (CS) activity and cytochrome c concentration measured independently from isolation yields. The state-3 respiration activity and isolation yield in the CA group declined significantly as compared to those in the sham group (brain, p < 0.01; kidney, p < 0.001). The CS activity in the CA group declined significantly as compared to that of the sham group (brain, p < 0.01; kidney, p < 0.01). Likewise, cytochrome c levels in the CA group had decreasing trends (brain, p = 0.08; kidney, p = 0.25). Conclusions CA decreased mitochondrial respiration activity and the quantity of mitochondria isolated from the tissues. Due to the nature of fragmented or damaged mitochondria membranes caused by this acute injury model, it is plausible that the mitochondrial function measured in the acute injury animal model might be underestimated.